Oscillate wildly : space, body, and spirit of millennial materialism - Hitchcock, Peter (University of Minnesota Press, 1999)
At a moment of crisis, in the wake of materialist practice once known as socialist revolution, this bold and innovative book presents oscillation as a metaphor for understanding materialism anew. Mindful of the dangers for materialism, Peter Hitchcock nevertheless shows how oscillation is part of the conceptual framework of materialist inquiry from Marx to the present.